Solar Powered IoT Flood Detector - Koh, Ming Ray; Mustafa, Farahiyah (Progress in Engineering Application and Technology, 2023)
Flooding has become common in Malaysia. These floods, which have been happening more and more often in a scary way over the past few years, have had a huge effect on the lives of both people and other living things. This disaster happened because there were not enough systems to detect and track floods. The goal of the research is to use the "Internet of Things" (IoT) to make a system that can detect and track floods. Solar panel were utilized as the power source for the system. Ultrasonic sensors were used as inputs when building hardware to find water and keep track of how much water was there. The information can also be shown on an LCD panel. This system relies on LoRa SX1826 transceiver to operate as a wireless connection for data transfer between the system and the sensor despite using two Arduino Uno microcontrollers. To obtain the most recent value of the water level, ESP8266 further serves as a conduit between the sensor and the smartphone. A buzzer has been installed as an alarm to warn users of the hazard when the water level rises to a risky level. A small-scale prototype experiment is used to verify the proposed system's accuracy and simulate real flood condition. The system is expected to provide real time water level measurement utilizing an LCD display and a Blynk smartphone notification. By having an efficient display and alerting system, quick action and precaution may be done to prevent loss of life and minimize flood disaster damages.